2017
DOI: 10.1002/slct.201700297
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Free Copper‐Catalyzed Cyano‐ and Alkynylstannylation of Arynes

Abstract: A carbon–carbon triple bond of arynes was found to undergo cyanostannylation with a tin cyanide under CuCN catalysis to afford diverse ortho‐cyanoarylstannanes in high yield. The copper catalyst was also effective for alkynylstannylation of arynes, and the resulting alkynylstannylated products were demonstrated to be convertible into biologically active compounds and a dye for dye‐sensitized solar cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Of note is that the yield and regioselectivity observed here are identical to those in the original report . Other than the palladium‐based transformations, 3 added to the C≡C bond of benzyne derived from 8 under copper catalysis (Table ) . Here again, removing volatiles after the 1st step is effective, giving ( o ‐alkynylphenyl)stannanes 9 a , 9 f , 9 t , and 9 w in good to high yields.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Of note is that the yield and regioselectivity observed here are identical to those in the original report . Other than the palladium‐based transformations, 3 added to the C≡C bond of benzyne derived from 8 under copper catalysis (Table ) . Here again, removing volatiles after the 1st step is effective, giving ( o ‐alkynylphenyl)stannanes 9 a , 9 f , 9 t , and 9 w in good to high yields.…”
Section: Resultssupporting
confidence: 79%
“…Here again, removing volatiles after the 1st step is effective, giving ( o ‐alkynylphenyl)stannanes 9 a , 9 f , 9 t , and 9 w in good to high yields. Interestingly, for example, 9 a was obtained in higher yield of 91%, compared to 70% yield of the original reaction starting with 3 a . To address the possible reason for the higher yield, how those used in the 1st step of the one‐pot reaction affect the 2nd step was examined (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 2-cyanophenylstannane (1l) 13 was convertible into a 24% yield of 3la, whereas the arylstannylation of 4-pyridylstannane (1m) did not proceed at all. Of note is that the reaction completely stopped at the single aryne insertion stage, irrespective of arylstannanes (1) employed, which implies that the tin-electron-deficiency of 3 is considerably reduced through the aryne insertion.…”
mentioning
confidence: 99%
“…We have demonstrated that a transient carbonÀ carbon triple bond of arynes is smoothly inserted into a SnÀ CN bond of a tin cyanide under copper catalysis. [26,27] For example, the cyanostannylation proceed successfully by treating tributyltin cyanide and benzyne, [28] generated by the Kobayashi method [29] (from 2-(trimethylsilyl)phenyl triflate and a fluoride ion), with copper(I) cyanide to give tributyl(2-cyanophenyl)stannane in 72 % yield (Scheme 23). No additional ligand is necessary for the smooth transformation, and thus widely available CuCN efficiently promoted the cyanostannylation of such symmetrical arynes as 2,3-naphthalyne and 4,5-dimethylbenzyne.…”
Section: Cyanostannylation Of Arynesmentioning
confidence: 99%